A native-like adult L2 Korean learner's agentive acquisition of Korean relative clauses. (October 2020) - Kang, Dae-Min
Aims and objectives: Despite considerable interest in second language (L2) relative clauses (RCs)—one of the most difficult grammatical structures to learn—and in learner agency, few research efforts have been made to investigate how the latter informs the acquisition of the former. The current study looks at a native-like adult L2 Korean learner's comprehension/production of Korean RCs and the trajectory of his acquisition of the RCs. Methodology: The research instruments consisted of RC comprehension/production tasks and autobiographic interviews. Data and analysis: The L2 learner's responses in the comprehension task and those in the production task (audio-recorded) were reviewed for their accuracy. The processes of analyzing the interview data involved labeling themes/concepts forming from the data and interlinking categories to create larger, more general categories. Findings: The results indicated that the L2 learner's performance on the tasks was native-like, and that he had actively exercised his learner agency which had dynamically interacted with context to achieve such native-likeness. Originality: This study distinguishes itself from the few previous studies on exceptional adult L2 learners by focusing on grammatical competence in relation to agency. Significance: The current interpretive study—which used autobiographical interviews to examine the dynamic trajectory of L2 RC acquisition—indicates the importance of an L2 learner's agency.